Knowledge and practices of conservative treatment of chronic kidney disease in the perception of elderly women - Monique de Freitas Gonçalves Lima; Kheyla Santos Nascimento; Eliane Maria Ribeiro de Vasconcelos; Cecília Maria Farias de Queiroz Frazão; Mariana Luiza de Acioly Rodrigues; Karla Pires Moura Barbosa; Francisca Márcia Pereira Linhares (Revista Gaúcha de Enfermagem)
ABSTRACT: Objective: to understand the knowledge and practices of conservative treatment of chronic kidney disease from the perspective of elderly women. Method: descriptive, qualitative study, carried out in a Nephrology outpatient clinic of a public referral hospital in the city of Recife (PE), Brazil, with 21 elderly women. Data collection took place between January and July 2023, through semi-structured interviews and composed of two guiding questions: “What do you understand about chronic kidney disease?” and “What care do you take in your treatment?”. The interviews were recorded and analyzed with the help of the Iramuteq® software. Manifest Content Analysis was used to analyze the data and presented through Descending Hierarchical Classification and Similarity Analysis. Results: five thematic categories were identified: difficulties in understanding and communicating about the health condition; superficial knowledge and insecurity about the severity of kidney disease; eating practices and dietary restrictions; self-care practices and health management; and monitoring of laboratory tests. Conclusion: the study identified that elderly women have limited knowledge about the conservative treatment of chronic kidney disease, influenced by social, economic and educational barriers. The need for accessible public policies and educational strategies to support this care is highlighted.